Strontium metabolism in the juvenile Lake Sturgeon, Acipenser fulvescens (Rafinesque, 1817), and further evaluation of the isotope as a marking tool for stock discrimination. (27th January 2016) - Carriere, B.; Gillis, D.; Halden, N.; Anderson, G.
Summary: Stock enhancement efforts have been used to aid in increasing dwindling population levels of Lake Sturgeon, Acipenser fulvescens, that are currently of conservation concern. Consistent monitoring of stock enhanced fisheries requires a reliable and reproducible method to mark stocked fish such that the success of such programs can be determined. Recently, stable isotopic marking of hard structures in fish has been developed in a variety of species, however, optimal marking conditions are less well understood. In this study the metabolism of strontium in juvenile Lake Sturgeon and determined parameters for optimisation of marking success in the fin ray were examined. Using radioactive strontium ( 85 Sr), whole body influx and efflux rates of strontium were 3.02 ± 0.364 pmol h −1 g −1 (mean ± standard error) and 0.04 ± 0.007 pmol h −1 g −1, respectively. Furthermore, short‐term accumulation of 85 Sr in a variety of tissues was assessed and found to be greatest in the fin ray. Biological half‐life of the stable isotope 86 Sr was shortest in muscle and longest in the fin ray tissue. Immersion and length of immersion timing had positive relationships with marking success. Additionally, the signature remained in 75% of fish analysed 550 days post‐mark. Data suggest that marking success was determined by duration of immersion in the mark and concentration of the mark introduced to the water.